MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DAN TIPE NHT TERHADAP KEAKTIFAN DAN HASIL BELAJAR SISWA - Maria Eflinda Suryati Lindung (Jurnal Riset Pembelajaran Matematika, 2021)
The purpose of this study is to determine whether there is a difference in the application of the cooperative learning model type STAD and type NHT on student activity and learning outcomes. This study uses a quantitative approach and the method used is an experimental method with data collection techniques using test and observation methods. The statistical test used was the multi-variate analysis of variance test. The result of this research is that there is a significant difference between the STAD and NHT cooperative learning models on student learning outcomes and activities.